2005
DOI: 10.1093/humrep/dei382
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and clinical outcome of 250 cycles of Preimplantation Genetic Diagnosis for single gene disorders

Abstract: Minisequencing for mutation detection combined with multiplex fluorescence PCR for linkage analysis is an efficient, accurate and widely applicable strategy for PGD of SGDs. Our experience provides a further demonstration that PGD is an effective clinical tool and a useful option for many couples with a high risk of transmitting a genetic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 51 publications
0
64
0
3
Order By: Relevance
“…Data showed that the second most frequent cause of FP diagnosis was ADO, an inherent pitfall of single-cell PCR. Strategies to overcome the technical limitations of single-cell PCR have been previously described 4,[16][17][18] and incorporated in the ESHRE best practice guidelines for monogenic PGD. 7 To preclude adverse misdiagnosis due to ADO and contamination, the co-amplification of linked polymorphic markers across the locus of interest is highly recommended and the advantages of the approach had been extensively described.…”
Section: Discussionmentioning
confidence: 99%
“…Data showed that the second most frequent cause of FP diagnosis was ADO, an inherent pitfall of single-cell PCR. Strategies to overcome the technical limitations of single-cell PCR have been previously described 4,[16][17][18] and incorporated in the ESHRE best practice guidelines for monogenic PGD. 7 To preclude adverse misdiagnosis due to ADO and contamination, the co-amplification of linked polymorphic markers across the locus of interest is highly recommended and the advantages of the approach had been extensively described.…”
Section: Discussionmentioning
confidence: 99%
“…It has proven to be accurate enough to detect single nucleotide substitutions in the context of PGD [24,25]. This technique allows us to interrogate the exact position of a nucleotide change, genotyping the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…As performing PGD, two blastomeres can be examined from one embryo at the same time, providing a double check for the results. It was reported that pregnancy and implantation rates did not appear to be significantly affected in spite of the biopsy of the two cells from embryos with 7 or more cells [31]. When the results of both blastomeres are identically normal, there is a high probability that the embryo will also be normal.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution is wider in patient's lymphocytes: some of the patient's lymphocytes were categorized as normal contrary to expectations. These results may be due to PCR amplification failure in duplicated exons in the same way as the phenomenon that results in the failure to amplify one allele of a heterozygous locus, commonly called allele drop-out, of which the rate ranges from 0 to 12.9% with the average rate taken to be 7.5% [31]. Amplification failure, which is a dangerous risk in PCR from single cells, can lead to a misdiagnosis, especially in gender determination.…”
Section: Discussionmentioning
confidence: 99%